“Non ci crediamo alla parola”. Il rizoma di Deleuze e il cinema di Deligny - Adesso, Gemma Bianca (Aesthetica Preprint, 2023)
It is not possible to fully explore the relationship between Gilles Deleuze and Fernand Deligny in a single essay. On the other hand, unlike other themes, the common interest of the two authors for cinema and in particular the role played by autistic images and cartography has remained largely unexplored. Through some research attempts, the first paragraph will compare the lives of the two Authors, focusing in particular on La Borde’s clinic and more generally on the need that both feel to create an alternative vocabulary made of images. Then the research will move on to Deligny’s cartography and cinematography, linking them to the concept of rhizome. In the last paragraph, Deligny’s anti-method will be compared with Deleuze’s visual antilogues: two perspectives which, no longer believing in Language, each become practical in its own way: cartographic, cinematographic, of reality.